Drug abuse prevention strategy in youth and student community in Indonesia - Handayani, Retty Dwi; Utari, Dyah (Journal of Youth and Outdoor Activities, 2024)
Background: The prevalence of drug abusers in the world is approximately 5%. Meanwhile, Indonesia in 2015 is estimated at 2.8%, which increases almost doubled in the last ten years. The most significant drug user is at the level of youngsters who live in urban areas. The treatment for the youngster cannot be done by just using the principle of law enforcement. A new strategy is needed. Methods: The objective of this study is to analyse some factors which quantitatively gives value to feasible priority approaches. The study is designed as a case study locally in Indonesia, exploring current drug abuse prevention efforts. The strategy proposed in this study is analysed using Analytical Hierarchy Process method. Findings: The recommended strategy offered to prevent drug abuse case is to intervene in the social media campaign. The primary action aims to raise community awareness concerning drug abuse. During this time, many policy approaches are ineffective due to lack of cooperation with related stakeholders and determination of prevention programme object through inappropriate media. Conlusions: To conclude, social media intervention, as the priority of drug prevention programme for youth and student community, should be well managed to be able to reduce drug abuse effectively.